2011
DOI: 10.1007/s10549-010-1322-0
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled trial (NCIC CTG MAP.2) examining the effects of exemestane on mammographic breast density, bone density, markers of bone metabolism and serum lipid levels in postmenopausal women

Abstract: We hypothesized that exemestane (EXE) would reduce mammographic breast density and have unique effects on biomarkers of bone and lipid metabolism. Healthy postmenopausal women were randomized to EXE (25 mg daily) or placebo (PLAC) for 12 months and followed for a total of 24 months. The primary endpoint was change in percent breast density (PD) between the baseline and 12-month mammograms and secondary endpoints were changes in serum lipid levels, bone biomarkers, and bone mineral density (BMD). Ninety-eight w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…The data regarding change in mammographic breast density in patients taking aromatase inhibitors are mixed. Two studies reported a significant decrease in mammographic breast density in women taking aromatase inhibitors [19,20], whereas randomized placebocontrolled trials of two different aromatase inhibitors found no difference in mammographic breast density at 6, 12, or 24 months compared with baseline [21,22]. Longer follow-up may be needed to assess the change in fibroglandular volume over time, including in our study, because our post-RRSO MRI median time was only 8 months.…”
Section: Discussionmentioning
confidence: 83%
“…The data regarding change in mammographic breast density in patients taking aromatase inhibitors are mixed. Two studies reported a significant decrease in mammographic breast density in women taking aromatase inhibitors [19,20], whereas randomized placebocontrolled trials of two different aromatase inhibitors found no difference in mammographic breast density at 6, 12, or 24 months compared with baseline [21,22]. Longer follow-up may be needed to assess the change in fibroglandular volume over time, including in our study, because our post-RRSO MRI median time was only 8 months.…”
Section: Discussionmentioning
confidence: 83%
“…55 A randomized study of another aromatase inhibitor, exemestane, versus placebo similarly found no significant change in percent density with treatment. 56 Endogenous sex hormones Studies aimed at testing the hypothesis that in postmenopausal women breast density reflects blood levels of sex hormones, found no association after BMI had been taken into account (women with high BMI have higher hormone levels and lower density levels). [57][58][59] In addition, the lack of association between density of the surrounding breast tissue and estrogen receptor (ER) status in breast cancer supports the hypothesis that density and postmenopausal endogenous estrogen levels are indepen dent risk factors.…”
Section: Breast Density and Breast Cancer Riskmentioning
confidence: 99%
“…decreasing breast density [14][15][16][17][18][19]. although much less data are available about the prognostic significance of decreasing breast density by ais as compared this data of tamoxifen.…”
Section: Breast Density and Recurrencementioning
confidence: 99%
“…The effects of ais on breast density in postmenopausal early breast cancer patients have mainly been investigated during or after treatment with the non-steroidal ais anastrozole and letrozole [14][15][16][17][18][19]. Data on the effect of the steroidal ai exemestane on breast density are limited.…”
mentioning
confidence: 99%